Structure–Activity Relationship of Novel Second-Generation Synthetic Cathinones: Mechanism of Action, Locomotion, Reward, and Immediate-Early Genes - Nadal-Gratacós, Nuria; Alberto-Silva, Ana Sofia; Rodríguez-Soler, Míriam; Urquizu, Edurne; Espinosa-Velasco, Maria; Jäntsch, Kathrin; Holy, Marion; Batllori, Xavier; Berzosa, Xavier; Pubill, David; Camarasa, Jordi; Sitte, Harald H.; et al. (Frontiers in Pharmacology, 2021)
Several new synthetic cathinones, which mimic the effect of classical psychostimulants such as cocaine or MDMA, have appeared in the global illicit drug market in the last decades. In fact, the illicit drug market is continually evolving by constantly adding small modifications to the common chemical structure of synthetic cathinones. Thus, the aim of this study was to investigate the in vitro and in vivo structure-activity relationship of six novel synthetic cathinones currently popular as recreational drugs, Pentedrone, Pentylone, N-ethyl-pentedrone (NEPD), N-ethyl-pentylone (NEP), 4-methyl-pentedrone (4-MPD) and 4-methyl-ethylaminopentedrone (4-MeAP), which structurally differ in the absence or presence of different aromatic substituents and in their amino terminal group. Human embryonic kidney cells (HEK293) expressing the human isoforms of SERT and DAT were used for the uptake inhibition and release assays. Moreover, Swiss-CD-1 mice were used to investigate their psychostimulant effect, rewarding properties (3, 10 and 30 mg/kg, i.p.) and the induction of immediate-early genes (IEGs) such as arc and c-fos in dorsal (DS) and ventral striatum (VS) as well as bdnf in medial prefrontal cortex (mPFC). Our results demonstrated that all tested synthetic cathinones are potent dopamine (DA) uptake inhibitors, especially the N-ethyl analogues, while the ring-substituted cathinones tested showed higher potency as SERT inhibitors than their no ring-substituted analogues. Moreover, unlike NEP, all tested compounds showed “hybrid” properties, acting as DAT blockers but SERT substrates. Regarding the locomotion, NEP and NEPD were more efficacious (10 mg/kg) than their N-methyl analogues, which correlates with their higher potency inhibiting DAT and an overexpression of arc levels in DS and VS. Furthermore, all compounds tested induced an increase in c-fos expression in DS, except for 4-MPD, the least effective compound at inducing hyperlocomotion. Moreover, NEP induced an up-regulation of bdnf in mPFC that correlates whit its 5-HTergic properties. Finally, the present study demonstrated for the first time that pentylone, NEP, 4-MPD and 4-MeAP induce reward in mice. Altogether, this study provides valuable information about the mechanism of action, psychostimulant and rewarding properties as well as changes in the expression of IEGs related to addiction induced by novel second-generation synthetic cathinones.